Fraud, Corruption and Sport - Brooks, G. author. aut Link
IX, 206 p.
Keywords: This book offers historical and contemporary international analysis of fraud and corruption in sport, including a diverse range of cases from the sporting world including football, cricket, horse racing and boxing.